Management of Spinal Tuberculosis (TB) in Developing Country - Mahadewa, Tjokorda G. B. (BALI MEDICAL JOURNAL, 2016)
Background: Tuberculosis on the spine is involved approximately 1 % of all tuberculosis cases. It is  a lethal type of TB skeletal due to highly neurologic compromised because of adjacent medullary  compression and incidence kyphotic deformity. Early diagnosis and management of this disease is  mandatory to prevent serious complications. Method: Serial case report was conducted in Sanglah  General Hospital from January 2014 until December 2015. All patients were diagnosed based on local  protocol using appropriate imaging technique. All patients were treated by anti-tuberculosis drugs for  2 weeks followed by functional assessment by MMT, ASIA, and JOA. Result: The author reported  10 patients of spinal TB whom were treated in Sanglah Hospital, Bali between January 2014- Desember 2015. Among pts 8 male and 2 female with location of spinal TB i.e 4 in thoracal, 4 in  lumbal and 2 in cervicothoracal. Preoperative ASIA scale was an average scale C and postoperative  ASIA scale was in D. The average JOA pre-surgical score was 10.5 and postsurgical was 14.5.  Improvement using the formula JOA achieved with an average of 21.6 %. All patients neurologically  improved, no complications and surgical implant failures in this series. Conclusions: Surgical  management of spinal tuberculosis, if delivered with appropriate indication, proved to be effective in  correcting spinal kyphosis. Early management is mandatory in order to ensure better prognosis.
Keywords: Spinal tuberculosis, management, pitfalls.